Kulturowe konsekwencje globalizacji - Mróz, Joanna (Cultural consequences of globalization., 2005)
Cultural problems of enterprises in the context of globalization has been presented in the paper. After defining the article’s keywords, the role of cross-cultural management has been discussed. Particularly the cultural implications of globalization for the company as a whole and for the single employee have been pointed out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 18-27